2014
DOI: 10.1007/s10549-014-3160-y
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral prophylactic mastectomy and its association with reduced mortality: evidence for selection bias

Abstract: Background Contralateral prophylactic mastectomy (CPM) refers to removal of the opposite uninvolved breast in women with unilateral breast cancer, and rates are increasing worldwide. In observational studies, CPM is often associated with reductions in breast cancer-specific and all-cause mortality, but this may reflect the selection of a healthier cohort of women for CPM (selection bias). To further explore this possibility, we examined the association between CPM and non-cancer mortality, an indicator of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The Cochrane Database, a meta-analysis, and other studies indicate no difference in OS or breast cancer–specific survival and cite selection bias as the cause of superior outcomes in the studies that demonstrated improvement in survival 22 , 31 , 32. A recent SEER analysis examined CPM’s effect not only on all-cause and breast cancer mortality but also on noncancer mortality 33. This study showed a greater reduction in noncancer mortality for CPM than for all-cause or breast cancer mortality and illustrates how selection bias likely accounts for the survival benefit reported from CPM.…”
Section: Contralateral Prophylactic Mastectomymentioning
confidence: 99%
“…The Cochrane Database, a meta-analysis, and other studies indicate no difference in OS or breast cancer–specific survival and cite selection bias as the cause of superior outcomes in the studies that demonstrated improvement in survival 22 , 31 , 32. A recent SEER analysis examined CPM’s effect not only on all-cause and breast cancer mortality but also on noncancer mortality 33. This study showed a greater reduction in noncancer mortality for CPM than for all-cause or breast cancer mortality and illustrates how selection bias likely accounts for the survival benefit reported from CPM.…”
Section: Contralateral Prophylactic Mastectomymentioning
confidence: 99%
“…26 Prophylactic contralateral mastectomy is a common request from patients who require a mastectomy on the affected side, or in lieu of breastconserving surgery. 28,29 It remains somewhat unknown as to the significant trend of patientdirected bilateral mastectomies, given the extensive data that supports breast-conserving surgery. 28,29 Rates of contralateral prophylactic mastectomy among this group of women are rapidly increasing; however, there are few published data that support this decision-making process for this more aggressive treatment with negative gene testing.…”
Section: Prophylactic Mastectomymentioning
confidence: 99%
“…28,29 It remains somewhat unknown as to the significant trend of patientdirected bilateral mastectomies, given the extensive data that supports breast-conserving surgery. 28,29 Rates of contralateral prophylactic mastectomy among this group of women are rapidly increasing; however, there are few published data that support this decision-making process for this more aggressive treatment with negative gene testing. 28,29 Researchers conducted semi-structured interviews with nine newly diagnosed patients who elected contralateral prophylactic mastectomy over other surgical options.…”
Section: Prophylactic Mastectomymentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the association between CPM and improved breast cancer outcomes, and determine if this association is possibly attributable to selection bias, we examined associations between CPM and breast cancer-specific, allcause, and non-cancer mortality utilizing multivariate logistic regression [20]. CPM would not be expected to reduce noncancer mortality, and any association between CPM and reduced non-cancer mortality would suggest that a healthier cohort of women were preferentially selected for CPM (selection bias).…”
mentioning
confidence: 99%